2023
DOI: 10.1039/d3np00006k
|View full text |Cite
|
Sign up to set email alerts
|

Structural diversity, hypothetical biosynthesis, chemical synthesis, and biological activity ofGanodermameroterpenoids

Abstract: This review comprehensively summaries the structure diversity and possible biosynthesis of representative Ganoderma meroterpenoids (GMs), as well as the chemical synthesis and pharmacological activities of some significant GMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 143 publications
(337 reference statements)
0
8
0
Order By: Relevance
“…Here, we identified ClaS as an atypical PHB-type UbiA PT using HYQ as the aromatic substrate. Thus, our study not only expanded the paradigm of prenyl-HYQ biosynthesis but also provided new insight into the biosynthetic pathways of meroterpenoids, like clavipines and clavilactones, and Ganoderma meroterpenoids . So far, only three UbiA PTs from macrofungi have been reported and they are all noncanonical UbiA-type terpene synthases including EriG from Hericium erinaceum and Tps1A and Tps2A from Antrodia cinnamomea .…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Here, we identified ClaS as an atypical PHB-type UbiA PT using HYQ as the aromatic substrate. Thus, our study not only expanded the paradigm of prenyl-HYQ biosynthesis but also provided new insight into the biosynthetic pathways of meroterpenoids, like clavipines and clavilactones, and Ganoderma meroterpenoids . So far, only three UbiA PTs from macrofungi have been reported and they are all noncanonical UbiA-type terpene synthases including EriG from Hericium erinaceum and Tps1A and Tps2A from Antrodia cinnamomea .…”
Section: Resultsmentioning
confidence: 75%
“…Thus, our study not only expanded the paradigm of prenyl-HYQ biosynthesis but also provided new insight into the biosynthetic pathways of meroterpenoids, like clavipines and clavilactones, 7 and Ganoderma meroterpenoids. 35 So far, only three UbiA PTs from macrofungi have been reported and they are all noncanonical UbiA-type terpene synthases including EriG from Hericium erinaceum 36 and Tps1A and Tps2A from Antrodia cinnamomea. 37 With the discovery of the atypical PHB-type UbiA PT, it is reasonable to predict that macrofungi may have more UbiA PTs with desirable catalytic functions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Ganoderma has attracted significant attention from pharmacologists, chemists, and phytochemists because it has long been used as a traditional medicine in many countries 1,2 and is also an important source of meroterpenoids and lanostane triterpenoids with significant bioactivities and captivating structures. 3–9 In particular, Ganoderma triterpenoids (GTs) have been widely studied as the main active constituents of Ganoderma for their anti-tumor, anti-aging, liver-protective, and neuroprotective activities. Notably, previous studies have confirmed that GTs can reverse cognitive impairment, 10 attenuate LPS-induced inflammation and apoptosis, 11 promote amyloid-β clearance and inhibit Tau pathology through activating autophagy, 6,12 suggesting that GTs exhibit huge potential in the treatment of neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…1 They have been discovered to exhibit diverse biological activities such as antibacterial, antifungal, anticancer, antioxidant and cytotoxic activities. 2 Hence, chemists have paid lots of attention to the development of efficient methods for constructing naphthofuran and chromane scaffolds. Diverse access to these two scaffolds has been realized, 3–6 of which the most important part involved the formation of the oxygen heterocyclic ring, namely furan ring and pyran ring.…”
Section: Introductionmentioning
confidence: 99%